Exploring Chromophore-Binding Pocket: High-Resolution Solid-State (1)H–(13)C Interfacial Correlation NMR Spectra with Windowed PMLG Scheme - Song, Chen (Springer Vienna, 2011)
High-resolution two-dimensional (2D) (1)H–(13)C heteronuclear correlation spectra are recorded for selective observation of interfacial 3–5.5 Å contacts of the uniformly (13)C-labeled phycocyanobilin (PCB) chromophore with its unlabeled binding pocket. The experiment is based on a medium- and long-distance heteronuclear correlation (MELODI–HETCOR) method. For improving (1)H spectral resolution, a windowed phase-modulated Lee–Goldburg (wPMLG) decoupling scheme is applied during the t (1) evolution period. Our approach allows for identification of chromophore–protein interactions, in particular for elucidation of the hydrogen-bonding networks and charge distributions within the chromophore-binding pocket. The resulting pulse sequence is tested on the cyanobacterial (Cph1) phytochrome sensory module (residues 1–514, Cph1Δ2) containing uniformly (13)C- and (15)N-labeled PCB chromophore (u-[(13)C,(15)N]-PCB-Cph1Δ2) at 17.6 T.